Oct-1 regulates IL-17 expression by directing interchromosomal associations in conjunction with CTCF in T cells - Kim, Lark Kyun (2014)
Interchromosomal associations can regulate gene expression but little is known about the molecular basis of such associations. In response to antigen stimulation, naïve T cells can differentiate into Th1, Th2 and Th17 cells expressing IFN-γ, IL-4 and IL-17, respectively. We previously reported that in naïve T cells, the IFN-γ locus is associated with the Th2 cytokine locus. Here we show that the Th2 locus additionally associates with the IL-17 locus. This association requires a DNase I hypersensitive region (RHS6) at the Th2 locus. RHS6 and the IL-17 promoter both bear Oct-1 binding sites. Deletion of either of these sites or Oct-1 gene impairs the association. Oct-1 and CTCF bind their cognate sites cooperatively and CTCF-deficiency similarly impairs the association. Finally, defects in the association lead to enhanced IL-17 induction. Collectively, our data indicate Th17 lineage differentiation is restrained by the Th2 locus via interchromosomal associations organized by Oct-1 and CTCF.